Beta-blocker effect on ST-segment: a prespecified analysis of the EARLY-BAMI randomised trial. Issue 2 (14th December 2020) - Fabris, Enrico; Hermanides, Renicus; Roolvink, Vincent; Ibanez, Borja; Ottervanger, Jan Paul; Pizarro, Gonzalo; van Royen, Niels; Mateos-Rodriguez, Alonso; Dambrink, Jan Henk; Albarran, Agustin; Fernández-Avilés, Francisco; Botas, Javier; et al.
Abstract : Objective: The effect of early intravenous (IV) beta-blockers (BBs) administration in patients undergoing primary percutaneous coronary intervention (pPCI) on ST-segment deviation is unknown. We undertook a prespecified secondary analysis of the Early Beta-blocker Administration before primary PCI in patients with ST-elevation Myocardial Infarction (EARLY-BAMI) trial to investigate the effect of early IV BB on ST-segment deviation. Methods: The EARLY-BAMI trial randomised patients with ST-elevation myocardial infarction (STEMI) to IV metoprolol (2×5 mg bolus) or matched placebo before pPCI. The prespecified outcome, evaluated by an independent core laboratory blinded to study treatment, was the residual ST-segment deviation 1 hour after pPCI (ie, the percentage of patients with >3 mm cumulative ST deviation at 1 hour after pPCI). Results: An ECG for the evaluation of residual ST-segment deviation 1 hour after pPCI was available in 442 out of 683 randomised patients. The BB group had a lower heart rate after pPCI compared with placebo (71.2±13.2 vs 74.3±13.6, p=0.016); however, no differences were noted in the percentages of patients with >3 mm cumulative ST deviation at 1 hour after pPCI (58.6% vs 54.1%, p=0.38, in BB vs placebo, respectively) neither a significant difference was found for the percentages of patients in each of the four prespecified groups (normalised ST-segment; 1–3 mm; 4–6 mm;>6 mm residual ST-deviation). Conclusions: In patients with STEMI, who were being transported for primary PCI, early IV BB administration did not significantly affect ST-segment deviation after pPCI compared with placebo. The neutral result of early IV BB administration on an early marker of pharmacological effect is consistent with the absence of subsequent improvement of clinical outcomes.